Research on Performance Evaluation under the "Corporate Sustainability Disclosure Standards": A Case Study of C&S (Journal of humanities and social sciences exploratio, 2026)
Against the backdrop of global sustainable development trends and China's Corporate Sustainability Disclosure Standards, integrating sustainability indicators into corporate performance evaluation systems has become an inevitable trend. The papermaking industry is a significant sector characterized by high energy consumption, severe pollution, yet possessing features of a circular economy. Therefore, this study focuses on papermaking enterprises, combines traditional performance metrics with ESG dimensions to develop an evaluation framework, employs the entropy weighting method for longitudinal performance assessment, and proposes targeted recommendations to support green development in the industry.
Keywords: Corporate Sustainability Disclosure Standards; Performance Evaluation; ESG